Genetic variants of genes involved in thiopurine metabolism pathway are associated with 6-mercaptopurine toxicity in pediatric acute lymphoblastic leukemia patients from Ethiopia - Ali, Awol Mekonnen; Adam, Haileyesus; Hailu, Daniel; Engidawork, Ephrem; Howe, Rawleigh; Abula, Teferra; Coenen, Marieke J. H. (Frontiers in Pharmacology, 2023)
Genetic variation in the thiopurine S-methyltransferase (TPMT) gene by and large predict variability in 6-mercaptopurine (6-MP) related toxicities. However, some individuals without genetic variants in TPMT still develop toxicity that necessitates 6-MP dose reduction or interruption. Genetic variants of other genes in the thiopurine pathway have been linked to 6-MP related toxicities previously. The aim of this study was to evaluate the effect of genetic variants in ITPA, TPMT, NUDT15, XDH, and ABCB1 on 6-MP related toxicities in patients with acute lymphoblastic leukemia (ALL) from Ethiopia. Genotyping of ITPA, and XDH was performed using KASP genotyping assay, while that of TPMT, NUDT15 and ABCB1 with TaqMan® SNP genotyping assays. Clinical profile of the patients was collected for the first 6 months of maintenance phase treatment. The primary outcome was the incidence of grade 4 neutropenia. Univariate followed by multivariate cox regression analysis was performed to identify genetic variants associated with development of grade 4 neutropenia within the first 6 months of maintenance treatment. In this study, genetic variant in XDH and ITPA were associated with 6-MP related grade 4 neutropenia and neutropenic fever, respectively. Multivariate analysis revealed that patients who are homozygous (CC) for XDH rs2281547 were 2.956 times (AHR 2.956, 95% CI=1.494-5.849, p=0.002) more likely to develop the grade 4 neutropenia than those with the TT genotype. In conclusion, in this cohort, XDH rs2281547 was identified as a genetic risk factor for grade 4 hematologic toxicities in ALL patients treated with 6-MP. Genetic polymorphisms in enzymes other than TPMT involved in the 6-mercaptopurine pathway should be considered during its use to avoid hematological toxicity.